2020
DOI: 10.1080/03075079.2020.1716322
|View full text |Cite
|
Sign up to set email alerts
|

What are inclusive pedagogies in higher education? A systematic scoping review

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication 1 What are Inclusive Pedagogies in Higher Education? A Systematic Scoping Review Abstract 'Inclusive pedagogies' have been recommended as an approach for addressing increased student diversity in the university classroom. However, to date, no research has sought to map the field of inclusive pedagogies in higher education (HE) to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 61 publications
0
38
0
9
Order By: Relevance
“…Moreover, they do their best to make sense of the learnings, thus fostering the meaningful learning of their students. In this sense, authors such as Love et al [54] have shown that, over master classes without interaction, students with disabilities prefer active and participatory methods, which is in line with the opinions of faculty members, who consider that these strategies help them to attend to the needs of these students [34].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, they do their best to make sense of the learnings, thus fostering the meaningful learning of their students. In this sense, authors such as Love et al [54] have shown that, over master classes without interaction, students with disabilities prefer active and participatory methods, which is in line with the opinions of faculty members, who consider that these strategies help them to attend to the needs of these students [34].…”
Section: Discussionmentioning
confidence: 70%
“…Unlike the above mentioned, the instruction models based on the constructivist theory consider the faculty member as a guide and an adviser, whose main role is not to transmit knowledge, but to facilitate and foster the construction of new learnings in the students [32,33]. These models are focused on the needs of the students, thus potentiating inclusive pedagogies [34]. Similarly, these participatory, active and collaborative methods are preferred by students, since they increase their motivation and participation, and generate a meaningful, accessible and relevant learning [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the integration of people with disabilities into the everyday life of society is of great importance (Chambers, 2015), which is largely due to the increased awareness of the value of human diversity (Shved, 2015). Studying the history of the development of inclusive practices (Stentiford, 2020) in the system of Ukrainian education makes the process of socialization of a person (Barkas et al, 2020) with disabilities effective (Martínez et al, 2020), based on an individual approach to everyone (Kolupaeva, 2009). To date, the so-called "inclusion without borders" (Lorraine et al, 2017), which implies the widespread implementation of joint learning, which often has a negative impact on the educational process, has become widespread (Gunn, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a growing interest is seen in this attribution in scientific literature that looks at the reforms undertaken by universities ( Larrán-Jorge and Andrades-Peña, 2017 ). Within this context, an important task assumed by higher education as part of its social responsibility is training in global citizenship skills ( Horey et al., 2018 ), but another very important subject is attending to individual and group diversity, particularly in reference to vulnerable groups, where universities design inclusive pedagogies ( Stentiford & Koutsouris, 2020 ) and other strategies oriented towards the pursuit of inclusion ( Baltaru, 2019 ). For example, they provide access to a greater number of citizens, but also qualify such access and promote personal, professional and social development among all groups of citizens ( Smith, 2020 ).…”
Section: Higher Education Diversity and Institutional Responsementioning
confidence: 99%